Pengalokasian Dana Bagi Hasil Dari Sumber Daya Alam Tambang Antara Pemerintah Pusat Dan Daerah - Fransiska N.G. Purba; Annisa Aprilia; Raka Anggara; Arsenius Felix Kusbintoro (Peneliti.net, 2023)
The enactment of Law No. 23/2014 on Regional Government, regulates the provisions of profit sharing funds, namely the acquisition of funds through state budget revenues and allocated to producing regions in terms of percentage digits to minimize disparities in financial capacity between the central and regional governments. Central finance refers to the financial management and administration of financial resources carried out by the central government or central institutions of a country. This entails the collection of revenues and expenditures, budget planning, financial supervision, and financial reporting related to the activities of the central government. Meanwhile, the Profit Sharing Fund is a profit sharing mechanism based on a predetermined percentage between the central and local governments. This money usually comes from sources of state revenue such as taxes, excise, or natural resource revenues. For national mining policy, it has a crucial value, resulting in regional autonomy becoming an added point for national mining policy makers, especially when accompanied by central and regional financial balance. This article examines more specifically the policies, problems, optimization and DBH system of mining natural resources.